Malaria mosquito resistance to agricultural insecticides: risk area mapping in Thailand - Overgaard, Hans (International Water Management Institute, 2006)
The purpose of this study was to identify risk areas in Thailand where insecticide resistance in malaria mosquitoes might develop as a consequence of crop protection activities in agriculture. The study provides guidelines on how to delineate risk areas. A review of insecticide resistance in disease vectors and the potential role of agricultural insecticides is presented.